The relationship between community type and community resilience. (October 2018) - Rapaport, Carmit; Hornik-Lurie, Tzipi; Cohen, Odeya; Lahad, Mooli; Leykin, Dima; Aharonson-Daniel, Limor
Abstract: Given the growing number of disastrous events around the globe in recent decades, much attention had been given to defining, measuring and enhancing resilience at the community level. In this study we examine if and to what extent does resilience vary among communities of different types. We use type of community as a proxy for social ties in the community, to examine variances in the perceived community resilience. We utilize an innovative measurement of community resilience, Conjoint Community Resilience Assessment Measure (CCRAM), which assesses five factors of perceived community resilience: leadership, preparedness, collective efficacy, trust and attachment to the place. Comparing between urban (n = 1345), suburban (n = 1239) and rural (n = 582) communities we found that rural communities showed the highest levels of community resilience factors, while urban communities the lowest. Furthermore, we examined possible predictors of community resilience and found that rural villages are a strong predictor of community resilience, as well as the sociodemographic categories: being older, sufficient or higher income and more religious. The results suggest that rural communities translate their strong social resources into perceived resilience. Finally, we raise suggestions for policy makers of creating resilient communities in cities on the basis of the rural model.